2006
DOI: 10.1111/j.1474-8673.2006.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic cholinoceptor activation modulates DNA synthesis and CD40 expression in fibroblast cells

Abstract: 1 The aim of the present work was to examine the role of muscarinic acetylcholine receptors (mAChR) on DNA synthesis and CD40 expression in human fibroblast cells. Neonatal human skin fibroblast cultures were stimulated with carbachol in presence or absence of specific antagonists and the following parameters were measured: identification of mAChR subtypes, DNA synthesis, inositol phosphates (InsP) production and CD40 expression. 2 Human fibroblasts express mAChR with Kd 0.47 +/- 0.11 nm and Bmax 236 +/- 22 fm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The increase in the apoptotic process is provoked by an activation of fibroblast‐mAChR M 1 and M 3 subtypes. Previously, by pharmacological analysis, we had shown that M 1 and M 3 mAChR subtypes were important mediators of mAChR agonist‐induced biological effects on human skin fibroblasts (Casanova et al, 2006), while M 2 and M 4 seemed to have no relevance in these actions. Depending on the receptor subtype and the cell type in which the receptor is expressed, G‐protein coupled receptors (GPCRs) can either induce apoptosis or protect cells from apoptotic stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the apoptotic process is provoked by an activation of fibroblast‐mAChR M 1 and M 3 subtypes. Previously, by pharmacological analysis, we had shown that M 1 and M 3 mAChR subtypes were important mediators of mAChR agonist‐induced biological effects on human skin fibroblasts (Casanova et al, 2006), while M 2 and M 4 seemed to have no relevance in these actions. Depending on the receptor subtype and the cell type in which the receptor is expressed, G‐protein coupled receptors (GPCRs) can either induce apoptosis or protect cells from apoptotic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Human fibroblasts express muscarinic acetylcholine receptors (mAChRs) of different subtypes (Carsi‐Gabrenas et al, 1997; Buchli et al, 1999). We demonstrated that mAChRs are expressed in human skin fibroblasts and their activation by carbachol induced an increment in DNA synthesis and in CD40 expression (Casanova et al, 2006). Pharmacological analysis with different mAChR antagonists allowed us to identify which of the known mAChR subtypes are active in human skin fibroblasts.…”
mentioning
confidence: 91%
“…Whether these effects are involved in the pathogenesis of chronic airway diseases remains to be elucidated. In human neonatal skin fibroblasts, mAChRs stimulate DNA synthesis and CD40 expression ( Casanova et al ., 2006 ).…”
Section: Cellular Functions Of Non‐neuronal Achmentioning
confidence: 99%
“…Other studies indicated that carbachol and pilocarpine act on skin fibroblasts via M1 and M3 (23,24). Skin melanocytes express a1, a3, a5, a7, b1, b2, g, and d in nicotinic AChRs and all muscarinic AChRs (19).…”
Section: Skinmentioning
confidence: 97%